Pengaruh Pelatihan M-Pise LPD Digital, Motivasi Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Di LPD Tegal Desa Darmasaba Badung Bali - Suryati, Ni Made; Kawiana, I Gede Putu; Astawa, I Putu Putra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Customer loyalty is a top priority for the company to survive amidst a tight barrier. The purpose of this study was to determine the effect of digital LPD m-pise training, motivation, and service quality on customer loyalty at LPD Tegal Desa Darmasaba Badung Bali partially and simultaneously. The population and respondents used in this study were 803 LPD Tegal customers with 89 respondents using the purposive sampling method. The data analysis technique used multiple linear regression analysis. Based on the analysis, it is found that M-Pise training has a positive and significant effect on customer loyalty, while motivation and service quality has a positive and insignificant effect on customer loyalty because the sig value is less than 0.05 and the t value is less than t table. The F test shows that the three independent variables jointly affect the customer loyalty variable. The suggestion in this research is for management to evaluate customer loyalty by looking at the M-Pise training factors, motivation, and service quality.